Revolutionizing Dental Education through Technology: A Comparative Study of Haptic Systems in Tooth Preparation Techniques - A double blinded randomized controlled trial - Kumar, Lakshay; Venugopalan, Suresh (Journal of Neonatal Surgery, 2025)
The evolution of dental education demands innovative tools that bridge the gap between theoretical knowledge and clinical competence. This double-blinded randomized controlled trial evaluated the efficacy of haptic virtual reality (VR) simulators compared to conventional mannequin-based methods in teaching tooth preparation skills to preclinical dental students. Ninety-six first-year Bachelor of Dental Surgery students with no prior clinical experience were randomly assigned to either a conventional training group (Group A) or a haptic VR training group (Group B). Both groups performed mandibular molar crown preparations, assessed on parameters including margin design, occlusal morphology, surface smoothness, undercuts, and total cut volume. Statistical analysis using the Mann–Whitney U test revealed significantly superior performance by the haptic VR group in margin design, undercut formation, and cut volume (p < 0.001), while the conventional group performed better in achieving smoother surfaces (p < 0.001). No significant difference was observed in occlusal morphology (p = 0.813). These findings underscore the potential of haptic VR simulators in enhancing precision and self-directed learning in preclinical settings, while highlighting the complementary value of conventional tactile training. A hybrid educational model integrating both approaches may offer a more comprehensive pathway to clinical readiness.